Energy savings measures in compressed air systems (2020)
Compressed air is one of the most widely used application energies in the industry, such as good transportability, safety, purity, cleanliness, storage capacity and ease of use. In many countries, compressed air systems account for approximately 10% of the industry’s total electricity consumption. Despite all its advantages, compressed air is expensive, only between 10% and 30% of the energy consumed reaches the point of final use. Energy is lost as heat, leaks, pressure drop, misuse, among others. Energy efficiency measures such as: reducing compressor pressure, lowering air inlet temperature, adequate storage capacity, recovering residual heat from the air compressor and reducing leakage, can produce energy savings between 20% and 60%, with an average return on investment lower than 2 years. This paper analyzes the main energy efficiency measures that can be applied in the CASs, the potential energy savings, implementation costs and return rate of each of them are being calculated giving a necessary tool for companies in their objectives to reduce greenhouse gas emissions and energy consumption.